PREFERENSI MAHASISWA TERHADAP PASANGAN CALON PRESIDEN DAN WAKIL PRESIDEN PADA PEMILIHAN UMUM 2024 - Sulfitri Husain; Nurhamni; Angga Angga (Journal Publicuho, 2025)
This study aims to analyze student preferences for presidential and vice presidential candidate pairs in the 2004 General Election. The background of this study is based on the importance of understanding the political preference patterns of the younger generation, especially students, as a strategic group in democracy. Student political preferences are influenced by various factors, including social media, policy issues, candidate leadership quality, and access to political information. This study uses a quantitative method with a survey approach. Data were collected through a questionnaire that had been tested for validity, involving 351 student respondents selected based on the Krejcie and Morgan Table. Data analysis was conducted to understand the pattern of student political preferences and the factors that influence their choices. The results of the study show that the majority of students tend to choose presidential and vice presidential candidate pairs who are considered to have high integrity, realistic work programs, and focus on education and employment issues. The personality factors of the candidates and leadership abilities are also major determinants of student preferences. These findings confirm that students have political preferences based on real needs and substantive policies, providing important implications for political campaign strategies that want to attract young voter segments.